TECHNIQUES AESTHETIC ACCEPTANCE OF MODERN LUMINAIRE IN THE PERSPECTIVE OF ATMOSPHERIC AESTHETICS - Jingjing, Mu; Vasylieva, Olena Serhiivna (Theory and practice of design, 2025)
Abstract. Рurpose. From the perspective of atmospheric aesthetics, this study explores the multi-level performance of modern luminaires in terms of aesthetic acceptance by analyzing the elements of light and shadow, color, and material in luminaire design. Methodology. A mixed-method approach was adopted, integrating qualitative and quantitative research. Surveys and interviews were conducted to understand user perceptions, while case studies of contemporary luminaire designs provided contextual insights. Additionally, computational simulations and lighting experiments were used to assess the impact of different lighting parameters on atmospheric aesthetics. Results. The findings reveal that factors such as light intensity, shadow dynamics, color temperature, and material textures significantly influence the aesthetic acceptance of modern luminaires. Users tend to prefer designs that create a harmonious spatial atmosphere and evoke specific emotional responses. The study also highlights a growing demand for adaptable and interactive lighting solutions that enhance environmental aesthetics. Scientific novelty. This research contributes to the study of atmospheric aesthetics by bridging lighting design with perceptual psychology. It proposes a new evaluation framework that moves beyond traditional stylistic and functional considerations, emphasizing the sensory and experiential dimensions of modern luminaires. Practical relevance. The study offers valuable insights for designers, architects, and manufacturers in creating luminaires that optimize both aesthetics and ambiance. The findings can be applied to residential, commercial, and public spaces, guiding the development of lighting solutions that enhance spatial perception and user experience.